Perancangan Design Thinking Tiket Dan Volunteer Eventvox Berbasis Website - Umairah, Mitha; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2024)
Ticket sales that are still done manually are a big challenge for event managers, as well as the Kalpataru Saka Organization Batam is a scouting organization that stands under the auspices of the Environmental Agency. This organization often holds events such as seminars, scouting competitions, workshops, and social services. With so many activities taking place, the committee finds it difficult to register participants and sell event tickets and recruit volunteers because it is still done manually so that there are many errors in registration and recruitment as well as in ticket sales which are not well organized so that sales are not stable. Therefore, the researcher will design a website that aims as a forum for selling event tickets and disseminating volunteer recruitment information in the Saka Kalpataru Batam organization by using design thinking as data processing, UML as system work modeling, and SDLC as system design processing. Studies show that the system can improve efficiency and user experience when managing events. All required features, such as event sales management, volunteer recruitment, and event and volunteer registration, can be accessed successfully through this website protocol. By determining data processing and system development properly, it will facilitate the system design process as in this study which uses design thinking as data processing so that it greatly facilitates the data collection process so that the website-based Eventvox platform is expected to later become a model for the development of other event management systems, and make a positive contribution to the event management industry.